Sole matrimonial property division through joint tenancy from shariah perspective / Hanizad Ramlan ... [et al.] - Ramlan, Hanizad; Abdul Aziz, Azhar; Sahari, Noorul Huda; Saidon, Rafeah (Universiti Teknologi MARA, 2022)
Currently the division of matrimonial property after death of spouse is proportionated according to spouse's contribution in acquiring the property. The share of deceased then be distributed to deceased heirs according to the legal portion provided by faraid law. This practice apparently could affect the interest of deceased spouse in the circumstance where the property of the spouse is only one asset particularly matrimonial home. The wife might lose the ownership of the home which resulted to the deceased wife lose her home to live. Moreover, the existing methods of distributions seem rigid and might take longer period to be settled. Thus, this study aims to examine the position of joint tenancy as a distribution of sole matrimonial property after spouse death from Shariah perspective and its practices in Malaysia. The study adopts qualitative methods where the data is collected from library resources including fiqh books, legal provisions and reported cases. The data was analysed using content analysis methods. The finding showed that joint tenancy is one of the instruments of estate planning for Muslims objectively to safeguard the interests of deceased spouse after the death of the spouse. The process of ownership and transfer of property will be implemented through the right of survivorship principle as well as facilitate the process of claims in shariah courts. It seems in line with the principles of maqasid syariah which prioritizes the maslahah of couples and children as well as avoiding disputes on the property between the deceased's heirs and the surviving co-owners.